Takotsubo syndrome vs anterior STEMI electrocardiography; a meta-analysis and systematic review. (1st November 2020) - Mir, Tanveer; Prakash, Preeya; Sattar, Yasar; Ahmad, Usman; Pervez, Eskara; Javed, Aamer; Khan, Muhammad Shayan; Ullah, Waqas; Pacha, Homam Mossa; Pahuja, Mohit; Lohia, Prateek; Alraies, M Chadi
ABSTRACT: Background: Takotsubo syndrome (TTS) and its differentiation from anterior wall ST-elevation myocardial infarction on electrocardiography (ECG) has been a debate. Methods: Six studies comparing ECG changes in TTS and AW-STEMI were identified. The primary endpoint was reciprocal changes, presence of Q-waves, and QT-interval. An unadjusted odds ratio (OR) with a 95% confidence interval (CI) was calculated using Review Manager (RevMan) 5.3. Results: Six studies consisting of 1090 patients (TTS = 220, AW-STEMI = 870) were included. Reciprocal changes on ECG were less commonly associated with TTS than AW STEMI with OR of 0.05 and 95%CI- 0.02–0.11 (P-<0.00001). Q-wave presence on ECG was comparable between the groups with OR-0.68, 95%CI-0.08–5.63 (p-0.72). QT interval on ECG was comparable between the two groups with OR-1.09, 95%CI-0.63–1.54 (p-<0.00001). There was minimal publication bias among the studies. Conclusion: AW STEMI is associated with reciprocal changes. Q-waves and QT interval has no differentiating significance between AW STEMI and TTS.